Application of insulin-like growth factor-1 in the treatment of inner ear disorders - Yamamoto, Norio; Nakagawa, Takayuki; Ito, Juichi (Frontiers in Pharmacology, 2014)
Sensorineural hearing loss is considered an intractable disease, given that hair and supporting cells of the postnatal mammalian cochlea are unable to regenerate. However, with progress in regenerative medicine in the 21st century, several innovative approaches for achieving regeneration of inner ear hair and supporting cells have become available. These methods include stem cell transplantation, overexpression of specific genes, and treatment with growth factors. Insulin-like growth factor 1 (IGF-1) is one of the growth factors that are involved in the development of the inner ear. Treatment with IGF-1 maintains hair cell numbers in the postnatal mammalian cochlea after various types of hair cell injuries, with activation of two major pathways downstream of IGF-1 signaling. In the aminoglycoside-treated neonatal mouse cochlear explant culture, promotion of the cell-cycle in supporting cells as well as inhibition of hair cell apoptosis was observed in the IGF-1-treated group. Activation of downstream molecules was observed in supporting cells and, in turn, supporting cells contribute to the maintenance of hair cell numbers. Using comprehensive analysis of the gene expression, the candidate effector molecules of the IGF-1 signaling pathway in the protection of hair cells were identified as Netrin1 and Gap43. Based on these studies, a clinical trial has sought to investigate the effects of IGF-1 on sensorineural hearing loss. Sudden sensorineural hearing loss that was refractory to systemic steroids was treated with IGF-1 in a gelatin hydrogel and the outcome was compared with a historical control of hyperbaric oxygen therapy. The proportion of patients showing hearing improvement was significantly higher in the IGF-1-treatment group at 24 weeks after treatment than in the control group. A randomized clinical trial is ongoing to compare the effect of IGF-1 treatment with that of intra-tympanic steroids for sudden sensorineural hearing loss that is refractory to system